Clinical trial for evaluation of Ricinus communis and sodium hypochlorite as denture cleanser - Maurício Malheiros BADARÓ; Marcela Moreira SALLES; Vanessa Maria Fagundes LEITE; Carolina Noronha Ferraz de ARRUDA; Viviane de Cássia OLIVEIRA; Cássio do NASCIMENTO; Raphael Freitas de SOUZA; Helena de Freitas de Oliveira PARANHOS; Cláudia Helena SILVA-LOVATO
Abstract The development of opportunistic infections due to poor denture hygiene conditions justified the search for effective hygiene protocols for controlling denture biofilm. Objective This study evaluated Ricinus communis and sodium hypochlorite solutions in terms of biofilm removal ability, remission of candidiasis, antimicrobial activity, and participant satisfaction. Material and Methods It was conducted a controlled clinical trial, randomized, double-blind, and crossover. Sixty-four denture wearers with (n=24) and without candidiasis (n=40) were instructed to brush (3 times/day) and immerse their dentures (20 min/day) in different storage solutions (S1 / S2: 0.25% / 0.5% sodium hypochlorite; S3: 10% R. communis; S4: Saline).The trial period for each solution was seven days and a washout period of seven days was used before starting the use of another solution. The variables were analyzed at baseline and after each trial period. The biofilm of inner surfaces of maxillary dentures was disclosed, photographed, and total and dyed areas were measured (Image Tool software). The percentage of biofilm was calculated. Remission of candidiasis was assessed by visual scale and score were attributed. Antimicrobial activity was assessed by the DNA-Checkerboard hybridization method. Patient satisfaction was measured using a questionnaire. Results S1 (4.41±7.98%) and S2 (2.93±5.23%) were more effective then S3 (6.95±10.93%) in biofilm remotion(P<0.0001). All solutions were different from the control (11.07±11.99%). S3 was the most effective solution in remission of candidiasis (50%), followed by S1 (46%). Concerning antimicrobial action, S1/S2 were similar and resulted in the lowest microorganism mean count (P=0.04), followed by S3. No significant differences were found with patient's satisfaction. Conclusions 10% R. communis and 0.25% sodium hypochlorite were effective in biofilm removal, causing remission of candidiasis and reducing the formation of microbial colonies in denture surfaces. All solutions were approved by patients.